Advancing pharmacogenetic testing in a tertiary hospital: a retrospective analysis after 10 years of activity - Stewart, Stefan; Dodero-Anillo, Jose Manuel; Guijarro-Eguinoa, Javier; Arias, Pedro; Gómez López De Las Huertas, Arturo; Seco-Meseguer, Enrique; García-García, Irene; Ramírez García, Elena; Rodríguez-Antolín, Carlos; Carcas, Antonio J.; Rodriguez-Novoa, Sonia; Rosas-Alonso, Rocio; et al. (Frontiers in Pharmacology, 2023)
The field of pharmacogenetics (PGx) holds great promise in advancing personalized medicine by adapting treatments based on individual genetic profiles. Despite its benefits, there are still economic, ethical and institutional barriers that hinder its implementation in our healthcare environment. A retrospective analysis approach of anonymized data sourced from electronic health records was performed, encompassing a diverse patient population and evaluating key parameters such as prescribing patterns and test results, to assess the impact of pharmacogenetic testing. A head-to-head comparison with previously published activity results within the same pharmacogenetic laboratory was also conducted to contrast the progress made after ten years. The analysis revealed significant utilization of pharmacogenetic testing in daily clinical practice, with 1145 pharmacogenetic tests performed over a one-year period and showing a 35% growth rate increase over time. Of the 17 different medical departments that sought PGx tests, the Oncology department accounted for the highest number, representing 58.47% of all genotyped patients. A total of 1,000 PGx tests were requested for individuals susceptible to receive a dose modification based on genotype, and 76 individuals received a genotype-guided dose adjustment. This study presents a comprehensive descriptive analysis of real-world data obtained from a public tertiary hospital laboratory specialized Eliminado: 4 40 Eliminado: 5 41 Movido (inserción) [1] Eliminado: 5 42